2018
DOI: 10.1177/1179547618791571
|View full text |Cite
|
Sign up to set email alerts
|

A Case of Obstructive Jaundice Caused by Metastasis of Ovarian Cancer to the Duodenal Major Papilla

Abstract: Ovarian cancer often occurs distant metastasis to the peritoneum, liver, lungs, and lymph nodes. However, there has been no reported case of direct metastasis to the duodenal major papilla. We herein reported 72-year-old woman with history of ovarian cancer surgery 11 years ago presenting with obstructive jaundice. Abdominal CT showed a small mass in the distal bile duct. Forceps biopsy from the small mass was done under endoscopic retrograde cholangiography, and histologic examination revealed adenocarcinoma.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
5
0
1

Year Published

2020
2020
2023
2023

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(6 citation statements)
references
References 14 publications
(19 reference statements)
0
5
0
1
Order By: Relevance
“…The most common sites of distant metastases for ovarian cancer are liver, lungs, peritoneum, and lymph nodes. 9 Takasaki et al reported a case of mechanical jaundice in an ovarian cancer patient with metastasis to duodenal major papilla and did not have any evidence of CDF. 9 Our patient had metastasis to the duodenum from ovarian cancer, resulting in a duodenal ulcer and subsequent CDF leading to pneumobilia, which to our knowledge is the first reported case.…”
Section: Discussionmentioning
confidence: 99%
“…The most common sites of distant metastases for ovarian cancer are liver, lungs, peritoneum, and lymph nodes. 9 Takasaki et al reported a case of mechanical jaundice in an ovarian cancer patient with metastasis to duodenal major papilla and did not have any evidence of CDF. 9 Our patient had metastasis to the duodenum from ovarian cancer, resulting in a duodenal ulcer and subsequent CDF leading to pneumobilia, which to our knowledge is the first reported case.…”
Section: Discussionmentioning
confidence: 99%
“…As BRCA1 and BRCA2 mutations are common risk factors for both ovarian and pancreatic cancers, pancreatic lesions should be evaluated by EUS-FNA to rule out the possibility of double cancers[ 238 ]. While MBO generally results from metastatic lymph nodes (Figure 3 ), obstructive jaundice due to metastasis to the major papilla has been reported[ 239 - 241 ]. Distal pancreatectomy has been reported as an option for cytoreductive surgery in advanced ovarian cancer in a study of six patients with pancreatic metastases[ 242 ].…”
Section: Primary Malignanciesmentioning
confidence: 99%
“…Metastasis Tumor yang menginduksi ikterus obstruktif sering disebabkan oleh metastasis hati, metastasis kelenjar getah bening, atau penyebaran peritoneum, dan sangat jarang oleh metastasis ke saluran empedu atau papilla. Selain itu, banyak kasus yang dilaporkan sampai saat ini menyatakan kanker payudara, kanker ginjal, atau melanoma ganas sebagai lesi utama (Takasaki et al, 2018…”
Section: Pendahuluanunclassified